2022
DOI: 10.3390/cryst12020173
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Hot Deformation Behaviour of Twin-Roll Cast AZ31 Magnesium Wire

Abstract: Due to their low density and high specific strength, magnesium alloys offer great potential as a design material for lightweight construction. An economical and energy-efficient method for the production of magnesium wire is the technology of twin-roll casting. In this work, the deformation behaviour of twin-roll cast and heat-treated AZ31 wire pre-profile is investigated for the first time during the compression test at different temperatures (250–400 °C) and forming speeds (0.01–10 s−1). To obtain optimal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…In contrast, the sample's middle exhibits equiaxed grains with segregations and precipitation zones between the grain boundaries. Similar results were found in previous studies [43] and for the AZ31 strips after twin-roll As the segregation region is enriched in probably Al or Zn, these regions may contribute to the formation of non-uniform grain sizes. It can be observed that at the edge of the sample, elongated, coarse grains are formed.…”
Section: Figure 2esupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, the sample's middle exhibits equiaxed grains with segregations and precipitation zones between the grain boundaries. Similar results were found in previous studies [43] and for the AZ31 strips after twin-roll As the segregation region is enriched in probably Al or Zn, these regions may contribute to the formation of non-uniform grain sizes. It can be observed that at the edge of the sample, elongated, coarse grains are formed.…”
Section: Figure 2esupporting
confidence: 91%
“…In contrast, the sample's middle exhibits equiaxed grains with segregations and precipitation zones between the grain boundaries. Similar results were found in previous studies [43] and for the AZ31 strips after twin-roll casting [25]. With the help of EDX analysis (measured in the sample center), it could be detected that the Mg 17 (Al, Zn) 12 precipitations and Al 8 Mn 5 particles are probably present (see Figure 3c).…”
Section: Figure 2esupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the hardening parameter n, in the literature, it is said that there is a creep of dislocation climb present n > 5 [48,49]. Therefore, it is concluded that the dislocation climb creep is the dominant mechanism for both alloys since AZ31 and AZ91 exhibit higher values than 5 (7.965, resp., 7.128).…”
Section: Hot Deformation Behaviormentioning
confidence: 98%